Architecture as Programmatic Archive: Sustainable Conservation on Tunjungan Street History - Bramasta Putra Redyantanu; Fulbert Otto (DIMENSI (Journal of Architecture and Built Environment), 2025)
This study presents a perspective where architecture can also designed as a model of archival representation in a historical urban space. It uses qualitative research-by-design and reflective architectural design methods, to consider Tunjungan Street's heritage as an exhibition space for contextual case for sustainable urban conservation through architectural thinking. The study identifies three principles: Movement as Program captures spatial movement to support walkability and more efficient use of resources; Heritage as Identity is about cultural character; and Urban Context as Sequence relates to social and ecological sustainability. Together, the principles structure design strategies that enable a reinterpretation of historical meaning-formally, in a material way—which represented progress for urban heritage interpretation through the lens of architectural programming. The study associated urban and sustainable growth to heritage design thinking through adaptive reuse, resilient heritage and socially engaged public places, making the case for the transformation of heritage design thinking as a model for the future. The study suggested a design-based model that positioned architectural programming as a strategic action for sustainable urban archiving, utilizing appropriation of exhibition strategies, and spatial sequencing as interpretations of the heritage of Tunjungan Street.